Laboratory manifestations and pathophysiological aspects of coronavirus disease 2019 pandemic: focusing on the digestive system. Issue Volume 33:Issue S1(2021) (13th December 2021) - Galanopoulos, Michail; Karianakis, Grigorios; Amorginos, Kyriakos; Doukatas, Aris; Gkeros, Filippos; Tsoukalas, Nikolaos; Papanikolaou, Ioannis; Viazis, Nikos; Liatsos, Christos
Abstract : Since December 2019, the severe acute respiratory syndrome coronavirus 2 has constituted a serious threat to global health. So far, there is little published evidence on the laboratory features of coronavirus disease 2019 (COVID-19). We have reviewed laboratory findings from multiple studies, mostly relating to the digestive system, since the virus outbreak. Laboratory data from older coronaviruses endemics, as well as other RNA viruses, were also reported. Although the main route of transmission is considered to be respiratory droplets, the distribution of ACE2 receptors in the gastrointestinal tract in combination with the detection of the virus in feces may imply a potential fecal–oral transmission route, and thus, emphasis should be given to patients with gastrointestinal symptoms. Interestingly, there is evidence that severe acute respiratory syndrome coronavirus 2 displays similar laboratory and clinical findings with older members of the coronavirus family, and so, comparable diagnostic and therapeutic approaches may be used. Regarding laboratory abnormalities, lymphopenia appears to be the most common finding, together with coagulation disorders and inflammatory markers elevation, reflecting a sustained systemic response. Abnormal liver and, occasionally, pancreatic tests are also common and even more severe in patients with gastrointestinal symptoms or diseases. Thus, the aim of this study is to focus on the laboratory and pathophysiologic side of this novel disease in order to strengthen current knowledge and urge further research. Detailed investigation of numerous studies may suggest a common laboratory pattern between COVID-19 patients. It is important for clinicians not to underestimate patients with gastrointestinal comorbidities, as they have been associated with severe COVID-19 disease.